2016
DOI: 10.1532/hsf.1505
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Intra-Myocardial Injection of Autologous Bone Marrow Mononuclear Cells Combined with Isolated Coronary Artery Bypass Grafting for Patients with Chronic Ischemic Heart Failure

Abstract: Intra-myocardial injection of aBMMNC transplantation on arrested heart during CABG is a safe procedure based on a longer period observation. The patients with chronic ischemic heart failure can benefit from aBMMNCs transplantation in the short-term (6 months) demonstrated by improved global LVEF compared with the control group; however, this additional benefit dimed with time as showed by 24-month clinical and echocardiographic follow-up results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Safety of BMMC treatment has been previously shown by us 11 and other studies 13 , and some studies have even shown reduced mortality in BMMC treated patients 8 . Yet, the trend of mortality, MACCEs or MACEs are not favorable for the treatment group—although none of these parameters resulted statistically significant.…”
Section: Discussionmentioning
confidence: 62%
“…Safety of BMMC treatment has been previously shown by us 11 and other studies 13 , and some studies have even shown reduced mortality in BMMC treated patients 8 . Yet, the trend of mortality, MACCEs or MACEs are not favorable for the treatment group—although none of these parameters resulted statistically significant.…”
Section: Discussionmentioning
confidence: 62%
“…These 4 literature [ 13 , 31 33 ] reports one trial. The final analysis included 22 independent RCTs [ 4 24 , 30 ]. A flow chart for the study selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are some points of view in previous studies. Wang et al [ 30 ] have commented that paracrine effects of BMMNCs transplantation and the intervention time may play a key role in the outcome, the left ventricular remodeling is more likely to be prohibited and the left ventricular systolic function obtains the opportunity to improve steadily in the long term while transplanted at the acute myocardial infarction setting, limited reduction in MI size, short-term improvement in LV function, and disappearance of paracrine effects over time when BMMNCs is transplanted at old myocardial infarction setting in which the left ventricular remodeling has already developed and the paracrine effect of BMMNCs is mainly acting on the transitional zone of old myocardial infarction. Wang et al [ 10 ] suggested that transplantation during off-pump coronary artery bypass grafts could reduce ischemia and reperfusion injury and restore vascular supply, thereby increasing stem cell survival rate and avoiding inflammation, loss of survival signal of extracellular matrix components and release of ischemic cardiac cytotoxic factors leading to high mortality of stem cells after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations